Contribution of hair density and hair diameter to the appearance and progression of androgenetic alopecia in Japanese men. (1st November 2014) - Ishino, A.; Takahashi, T.; Suzuki, J.; Nakazawa, Y.; Iwabuchi, T.; Tajima, M.
Summary: Background: Androgenetic alopecia (AGA) is the most common type of baldness in men. The balding process is associated with the gradual miniaturization of hair follicles and successive hair loss. However, the relative contributions of hair density and diameter to AGA are still unclear. Objectives: Hair density and hair diameter were investigated in Japanese men with or without AGA to elucidate the importance of these factors in the balding process. Methods: Male Japanese subjects with or without AGA ( n = 369) were included in this study. Hair appearance at the vertex was evaluated by comparison with a series of standard photographs. Hair density was measured using a phototrichogram‐based videomicroscopy technique, and hair diameter was assessed by comparison with a series of calibrated threads on the phototrichogram image. Results: All subjects with AGA were ≥ 25 years of age. The mean percentage of thick hairs (> 80 μm) in all subjects with AGA was significantly lower than that in subjects without AGA aged ≥ 25 years ( P < 0·01), but the mean percentage of vellus hairs (< 40 μm) in subjects with AGA was significantly higher ( P < 0·001). By contrast, the mean density of the hair in all patients with AGA did not significantly differ from the density of those without AGA aged ≥ 25 years. However, the mean density of the hair in subjects without AGA aged < 25 years was significantly higher than that of both subjects without AGA aged ≥ 25 years ( P < 0·001) and all subjects with AGA. Conclusions: Hair loss in men with AGA results mainly from the miniaturization of hair follicles rather than the loss of hair (shedding), at least for individuals who are ≥ 25 years of age and present with AGA.